Learning and Context: Connections in Teacher Professional Development - Barbara J. Daley (Adult Education Research Conference, 2004)
This qualitative interpretivist study analyzes the interrelationships between, the knowledge gained in teacher professional development programs and the context of employment. Findings indicate that teachers construct a knowledge base by moving back and forth between continuing education programs and their professional practice. Implications for research and practice are drawn.